2022
DOI: 10.1038/s41598-022-18868-4
|View full text |Cite
|
Sign up to set email alerts
|

Trait emotional intelligence in American pilots

Abstract: There is a dearth of trait emotional intelligence (trait EI) research within an aviation context. Using the Trait Emotional Intelligence Questionnaire (TEIQue), the present study investigated potential trait EI differences between pilots and general population controls in the United States. The forty-four pilots who volunteered to participate were primarily male (93%) and between 24 and 67 years with a wide range of flight experience (150–5000 + hrs.) They were matched with controls based on age, gender, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…For example, Military should have higher Selfcontrol scores as it is important in this line of work to able to regulate external pressures and stress. Actually, in a similar line of work, Dugger et al (2022) found that Pilots did not score lower than the US general population on the Self-control factor of trait EI. What is more, the trait EI profiles in certain professions may indirectly affect other individuals.…”
Section: Trait Emotional Intelligence Profiles Across Professions In ...mentioning
confidence: 80%
“…For example, Military should have higher Selfcontrol scores as it is important in this line of work to able to regulate external pressures and stress. Actually, in a similar line of work, Dugger et al (2022) found that Pilots did not score lower than the US general population on the Self-control factor of trait EI. What is more, the trait EI profiles in certain professions may indirectly affect other individuals.…”
Section: Trait Emotional Intelligence Profiles Across Professions In ...mentioning
confidence: 80%
“…Other researchers have analysed the specificity of certain occupational groups due to TEI. Dugger et al. (2022) studied differences in TEI of American pilots in relation to the US population.…”
Section: Methodsmentioning
confidence: 99%
“…Other researchers have analysed the specificity of certain occupational groups due to TEI. Dugger et al (2022) studied differences in TEI of American pilots in relation to the US population. Petrides et al (2022) determined TEI levels among surgeons in the UK A little earlier, TEIQue was used to analyse TEI ballet dancers and musicians (Petrides et al, 2006).…”
Section: Questionnairementioning
confidence: 99%
“…Historically, key components of a pilot skillset have included characteristics such as mental toughness and stress management. A study examining emotional intelligence (EI) in professional pilots indicated that pilots feel less emotional connectivity compared to the U.S. population (Dugger, et al, 2022). While flying, professional pilots are required to manage emotions, assess risk, make informed decisions, and operate in a stressful environment and may function well with lower levels of global trait EI than their non-pilot counterparts (Dugger, et al, 2022).…”
Section: Performance-based Acceptance and Commitment Training In A Co...mentioning
confidence: 99%
“…A study examining emotional intelligence (EI) in professional pilots indicated that pilots feel less emotional connectivity compared to the U.S. population (Dugger, et al, 2022). While flying, professional pilots are required to manage emotions, assess risk, make informed decisions, and operate in a stressful environment and may function well with lower levels of global trait EI than their non-pilot counterparts (Dugger, et al, 2022). Notably, pilots scored lower in three areas of the global trait EI: 1) emotionality, 2) sociability, and 3) well-being.…”
Section: Performance-based Acceptance and Commitment Training In A Co...mentioning
confidence: 99%